Die Politik der Deutschen Bundesbank in dem Konjunkturzyklus 1964 bis 1968 - Henner Kleinewefers (Kredit und Kapital, 1970)
The Policy of the German Bundesbank in the Trade Cycle from 1964 to 1968 This article examines the monetary policy of the German Bundesbank in the period from 1964 to 1968. 'The first chapter deals with the trend of macroeconomic magnitudes from 1964 to 1968. Special emphasis is placed on the exact fixing of trade cycle turning points, as this is of decisive importance for an assessment of monetary policy. In the second chapter, the individual measures taken by the Bundesbank are investigated. The customary consideration of minimum reserve policy and the granting of Bundesbank credit to the banks is summarized in a particularly significant ventilation of the "net cash position" of the banks in relation to the Bundesbank. A further section of this chapter covers the influence exerted by the Bundesbank on the interest rates for short and long term capital. In this connection special emphasis is placed on the relationship between interest and liquidity policy. The third chapter contains a comparison between the influence of the Bundesbank on monetary and trade cycle developments and other circumstances which exert a simultaneous effect, but cannot be influenced by the Bundesbank. The following are the most important results of this analysis: 1. The restrictive monetary policy of the Bundesbank was very mild, both absolutely and in comparison with other moneytightening factors. Therefore responsibility for the recession in late 1966 and the first sıx months of 1967 cannot be ascribed to the Bundesbank. 2. Since as early as midd-1966, the Bundesbank has permitted a marked improvement in the liquidity of the banking system by reversal of the balance of payments trend and from the beginning of 1967 it has energetically supported that improvement in liquidity. There is therefore no evidence that the Bundesbank delayed or hindered the new upswing of the trade cycle. These results contradict many of the charges levelled against the policy of the Bundesbank ın 1966 und 1967.
Keywords: 330